Suntentabilidade fiscal dos estados brasileiros no período de 1985 A 2008 - França, Celma Marta Carneiro Tapeti (2009)
This study assesses Brazilian States’ fiscal sustainability over the period 1985-2005 using Lin, Levin & Chen (2002) and Im, Pesaran & Shin (2003) panel unit roots tests. Although there is a great concern over habitual deficits in State government, the results show that their fiscal policies are sustainable.